Hydrodynamic Analysis of a Modular Integrated Floating Structure System Based on Dolphin-Fender Mooring - Nianxin Ren; Yuekai Yu; Xiang Li; Jinping Ou (Journal of Marine Science and Engineering, 2022)
For both the expansion of important islands/reefs and the development of marine resources in South China Sea, a modular integrated floating structure (MIFS) system with tidal self-adaptation dolphin-fender mooring (DFM) has been proposed. The DFM, coupled with wave energy converters (WEC), can serve as an anti-motion system. Considering both the modules’ hydrodynamic interaction effect and the connectors’ mechanical coupling effect, both dynamic responses of the MIFS system and the WEC’s output power characteristics were investigated under typical sea conditions. Based on the comprehensive consideration of key factors (safety, economy, and comfort), the effects of both the DFM and module connectors were systematically studied for the MIFS system. Preliminarily optimal design parameters of corresponding connectors and WECs were suggested. The security of the MIFS system under extreme sea conditions was checked, and a promising survival strategy has been proposed. In addition, the modular expansion scheme of the MIFS system was further discussed, and the results indicated that the proposed MIFS system shows good expansibility. The WEC can not only improve both dynamic responses and the comfort of inner modules, but also make considerable wave energy contributions.